External debt : definition, statistical coverage and methodology : a report (Published on behalf on the International Monetary Fund, the World Bank, the Bank for International Settlements, and the Organisation for Economic Co-operation and Development by OECD Publications, 1988)
Deals with the formulation of the "core definition" and reviews outstanding issues. Describes (BIS, IMF, OECD, IBRD), reproducing specimen tables from their main publications.